Synthesis of Unsaturated 5(4H)-Oxazolone Derivatives in the Presence of Antimony Pentafluoride as Catalyst - HAMIDIAN, HOOSHANG; MOMENI TIKDARI, AHMAD (Asian Journal of Chemistry, 2010)
Unsaturated 2-phenyl-5(4H)-oxazolone derivatives (azlactons) are the important class of synthons. Antiomony pentafluoride efficiently catalyzed the synthesis of unsaturated 2-phenyl-5(4H)-oxazolone derivatives under solvent-free conditions with microwave irradiation.